Das Frauenbild im Judentum der hellenistischen Zeit : ein Beitrag anhand von 'Joseph und Aseneth' - Standhartinger, Angela. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1995)
Each of the two reconstructed "oldest texts" of the intertestamental work, Joseph and Aseneth , presents a consistent picture with a coherent theology, but there are considerable differences between them. The image of women in each case serves to crystallise these differences, and their analysis opens a window not only on the texts but also on their social contexts. The author develops a method which allows close study of ancient literary images of women and of their effects on ancient readers. It is shown that the different images portrayed in the two versions correspond to differing trends in the pagan and Jewish environment and in Jewish-Hellenistic interpretations of the Bible. A controversy of social and theological importance emerges.